Enhancing Educational Quality through Strategic Philanthropy: A Case Study of LAZISMU Umbulharjo, Yogyakarta - Rina Khaerunnisa; Khayyun Latifah; Nadiya Shofiyah; Arlin Prima Sari; Bagas Ardyo Pradana (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – This study aims to analyze the role of the LAZISMU Umbulharjo Philanthropic Institution in enhancing educational quality within Umbulharjo Subdistrict, Yogyakarta. Design/methods– Employing a qualitative descriptive research design, this study conducted field observations, semi-structured interviews, and document analysis between March 7, 2023, and April 2, 2023. Primary and secondary data were gathered from the LAZISMU Umbulharjo office and its staff, particularly the Head of the LAZISMU Office. Findings – LAZISMU Umbulharjo, established in 2015, has made significant strides in advancing educational quality through various programs, including the Mentari Scholarship, Sang Surya Scholarship, and Peduli Guru initiative. These programs focus on different aspects of education, from scholarship provision to teacher training and facility enhancement. Research implications/limitations – This study highlights the potential of philanthropy in educational development. However, it is limited to one philanthropic entity in a specific locale, suggesting the need for broader research across diverse settings. Practical implications – The findings indicate that comprehensive and community-focused philanthropic approaches can effectively address educational inequalities and foster sustainable development. Originality/value – This study contributes to understanding philanthropic institutions' role in enhancing education quality, offering insights for policymakers and educational stakeholders in implementing similar initiatives.